Pendidikan Kesehatan tentang Insomnia pada Lansia di Panti Sosial Tresna Werdha Kota Bengkulu - Andrianto, Muhammad Bagus; Fatsiwi Nunik Andari; Andri Kusuma Wijaya (Jurnal Pengabdian, 2024)
Sleep health is an important concern in the aging population due to the common insomnia problem that older adults often face. This community service program aims to provide health education regarding insomnia to the elderly in the community. Through a series of seminars and workshops, participants will be provided with information about the causes, symptoms, and impacts of insomnia. In addition, the program will also offer practical insomnia management strategies and techniques, including implementing healthy sleep patterns, stress management, and the use of non-pharmacological therapies. The methods used include interactive presentations, group discussions, and relaxation exercises. It is hoped that through this program, seniors can increase their knowledge about insomnia and be able to implement steps to manage and reduce insomnia symptoms, thereby improving their sleep quality and overall quality of life.